Spatial Planning in Environmentally Valuable Areas in the Context of Public Participation on the Example of Czechów Hills in Lublin - Kamila Boguszewska; Natalia Przesmycka (Barometr Regionalny)
The area of “Górki Czechowskie” is in the north-western part of Lublin. Originally it was used as a military training field. In the Study of Directives on the Spatial Development of Lublin(which has been currently displayed for public viewing) it is supposed to be a green area surrounded by multi-family housing with services. Currently, this study sparks numerous controversies and protests of local residents and non-governmental organizations. In Lublin, there is currently a discussion on the appropriateness and applicability of the solutions included in the document. The article presents the problems of the issue and the role of resident participation in the process of spatial planning.